The Effect of Incentives in Non-Routine Analytical Team Tasks - Evidence From a Field Experiment - Florian Englmaier; Stefan Grimm; David Schindler; Simeon Schudy (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
Despite the prevalence of non-routine analytical team tasks in modern economies, little is known about how incentives influence performance in these tasks. In a field experiment with more than 3000 participants, we document a positive effect of bonus incentives on the probability of completion of such a task. Bonus incentives increase performance due to the reward rather than the reference point (performance threshold) they provide. The framing of bonuses (as gains or losses) plays a minor role. Incentives improve performance also in an additional sample of presumably less motivated workers. However, incentives reduce these workersẃillingness to ëxploreöriginal solutions.
Keywords: C92; C93; J33; D03; M52; 330; team work; bonus; incentives; loss; gain; non-routine; exploration